2012
DOI: 10.1016/j.jamda.2011.09.004
|View full text |Cite
|
Sign up to set email alerts
|

Antidepressant Prescribing Patterns in the Nursing Home: Second-Generation Issues Revisited

Abstract: Introduction The object of this study1 was to provide an updated evaluation of the quality of antidepressant management and prescribing patterns in nursing homes in the context of organizational and resident factors. Design Pearson correlation and chi-square analyses were conducted using information gathered from random nursing home charts. Setting Nursing home facilities in and around the Louisville, KY metropolitan area (N = 10). Participants Chart reviews were randomly chosen for 20% of long-term care… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
16
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 30 publications
3
16
0
Order By: Relevance
“…This may well be the case in the present study, as 33% of all participants without diagnosed depression or a CSDD score of ࣙ8 were prescribed antidepressants, without an obvious indication, which is also consistent with another study (Shah et al, 2012).…”
Section: Discussionsupporting
confidence: 93%
“…This may well be the case in the present study, as 33% of all participants without diagnosed depression or a CSDD score of ࣙ8 were prescribed antidepressants, without an obvious indication, which is also consistent with another study (Shah et al, 2012).…”
Section: Discussionsupporting
confidence: 93%
“…Furthermore, of the 6091 subjects included in this study, none reported taking antidepressants or receiving psychotherapy. However, the reported prevalence of antidepressant use in the United States ranges from 46–60% 45 . In Europe, this prevalence ranges from 23–45% 46 , and in Australia, the prevalence ranges from 21–33% 47 .…”
Section: Discussionmentioning
confidence: 99%
“…However, depression is an independent risk factor for all-cause mortality in nursing homes [9] and it has been suggested that underuse of antidepressants is associated with increased disability, worsening of clinical outcomes and increased mortality [10]. Present guidelines recommend antidepressants and specifically selective serotonin reuptake inhibitors (SSRIs) as the first-line treatment of depression in older patients [11,12]. Previous studies have documented that prescription rates of psychotropic medications in NHs may be influenced by facility factors including the presence of a professional geriatrician [13].…”
Section: Introductionmentioning
confidence: 99%